2022
DOI: 10.7759/cureus.32179
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Sildenafil Mortality Through the Years

Abstract: Sildenafil is a medication used for the treatment of erectile dysfunction. It was approved by the U.S. Food and Drug Administration (FDA) in 1998. Several articles have raised concerns regarding the use of sildenafil and the occurrence of serious adverse events, such as myocardial ischemia, stroke, and even death. Our aim is to systematically review the existing literature on mortality associated with sildenafil use. The method used for this systematic review was completed by searching three databases: PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…One claims analysis found that men with ED and PDE5I exposure were associated with 25% lower risk of overall mortality (hazard ratio, 0.51; P < .001) as compared with men with ED and no exposure to PDE5Is, 25 while a systematic review concluded that the existing literature is insufficient to establish causality between sildenafil and mortality. 26 However, a previous study examining CV AEs for PDE5Is in the FAERS database between 2000 and 2010 revealed that deaths represented 12.3% of the total sildenafil AEs while the current study found 9.88%. 27 As sildenafil is the oldest and one of the most used PDE5Is, a larger proportion of patients with comorbidities that have a significantly increased risk of death may be using sildenafil (although this study’s definition of death excluded death directly related to disease).…”
Section: Discussioncontrasting
confidence: 68%
“…One claims analysis found that men with ED and PDE5I exposure were associated with 25% lower risk of overall mortality (hazard ratio, 0.51; P < .001) as compared with men with ED and no exposure to PDE5Is, 25 while a systematic review concluded that the existing literature is insufficient to establish causality between sildenafil and mortality. 26 However, a previous study examining CV AEs for PDE5Is in the FAERS database between 2000 and 2010 revealed that deaths represented 12.3% of the total sildenafil AEs while the current study found 9.88%. 27 As sildenafil is the oldest and one of the most used PDE5Is, a larger proportion of patients with comorbidities that have a significantly increased risk of death may be using sildenafil (although this study’s definition of death excluded death directly related to disease).…”
Section: Discussioncontrasting
confidence: 68%
“…Our study showed an off‐target effect of the NDPPC, which augments the 4F‐induced cell cycle through inhibition of p38 MAP kinase. Off‐target effects of small molecules have been identified before in several studies, which might result in toxicity or other side effects (Al Ibrahim et al, 2022; Rudmann, 2013; Salmasi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed an off-target effect of the NDPPC, which augments the 4F-induced cell cycle through inhibition of p38⍺ MAP kinase. Off-target effects of small molecules have been identified before in several studies, which might result in toxicity or other side effects (Al Ibrahim et al, 2022;Rudmann, 2013;Salmasi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%